The City in Songs, Songs in the City: The Image of London in the Music of the 1970s and 1980s - Žáčková, Lucie (Univerzita Pardubice, 2018)
This bachelor thesis analyzes the image of London described in songs from the 1970s and 1980s. The first chapter explores what a city is and what notions are connected with the term. The second chapter describes the historical and cultural background of London in the second half of the twentieth century in order to provide a relevant basis for the following analysis. The analysis consists of three chapters, each one portraying an aspect of the image of London such as a torpid prison, a place of decay and a dream come true. The whole thesis is concluded with a chapter summarizing the overall image of London in the two decades.
Město v písních, písně ve městě: Obraz Londýna v hudbě 70. a 80. let dvacátého století
Keywords: Londýn; zobrazení; texty písní; společnost; 1970; 1980; London; image; lyrics; society; 1970s; 1980s